2016
DOI: 10.1287/moor.2015.0761
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Transient Price Impact and Matrix-Valued Positive Definite Functions

Abstract: We consider a model for linear transient price impact for multiple assets that takes cross-asset impact into account. Our main goal is to single out properties that need to be imposed on the decay kernel so that the model admits well-behaved optimal trade execution strategies. We first show that the existence of such strategies is guaranteed by assuming that the decay kernel corresponds to a matrix-valued positive definite function. An example illustrates, however, that positive definiteness alone does not gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 36 publications
3
50
0
Order By: Relevance
“…in agreement with Proposition 3.7. (b) of Alfonsi et al [2016] and equivalent to the condition for a symmetric 2 × 2 matrix to be positive-semidefinite.…”
Section: Symmetry Of Cross-impactmentioning
confidence: 99%
See 1 more Smart Citation
“…in agreement with Proposition 3.7. (b) of Alfonsi et al [2016] and equivalent to the condition for a symmetric 2 × 2 matrix to be positive-semidefinite.…”
Section: Symmetry Of Cross-impactmentioning
confidence: 99%
“…Note that this excludes kernels where for some ij G ij (0) = 0 but G ij (τ ) > 0 for some τ > 0. Indeed Example 3 in Alfonsi et al [2016] has a kernel that is asymmetric for τ > 0 and which does not allow price manipulation.…”
Section: Exponential Decaymentioning
confidence: 99%
“…The first two properties are extremely important in the calibration of cross-impact models, as shown in [AKS16,SL18]: to perform pricing within a cross-impact setup, the matrix Λ should be SPD in order to ensure absence of price manipulation. This is not the case for a MLE, which is thus not suitable for practical purposes.…”
Section: Consistency Of Correlationsmentioning
confidence: 99%
“…Existence of an optimal liquidation strategy in their model is guaranteed if the decay kernel corresponds to a matrix-valued positive definite function but additional assumptions on the decay kernel are required for the optimal liquidation strategies to be well-behaved. In their recent paper, Schneider and Lillo [20] established necessary conditions on the size and impact of cross-impact for the absence of dynamic arbitrage in a continuous time version of [1] that can be directly verified on data.…”
Section: Introduction and Overviewmentioning
confidence: 97%
“…He characterized the value function as the solution to the two-dimensional PDEs and showed that the optimal portfolio process depends only on the co-variance and crossasset market impact of the assets in his setting. Alfonsi et al [1] considered a discrete-time model of optimal basket liquidation with linear transient price impact and general deterministic resilience. Existence of an optimal liquidation strategy in their model is guaranteed if the decay kernel corresponds to a matrix-valued positive definite function but additional assumptions on the decay kernel are required for the optimal liquidation strategies to be well-behaved.…”
Section: Introduction and Overviewmentioning
confidence: 99%